The end of UMNO? essays on Malaysia's former dominant party : new and expanded post GE-14 edition - Welsh, Bridget 1967-; Funston, N. J. (N. John); Kessler, Clive S. 1942-; Chin, Ung-Ho 1967- (Strategic Information and Research Development Centre, 2018)
What is the future of Malaysia's former dominant party, the United Malays National Organisation or UMNO? With the loss of government in the May 2018 General Election (GE14) after 61 years in government, the party faces a different, more uncertain future. It is grappling with its new role in the national political opposition and continued questions about the leadership of former prime minister Najib Tun Razak. This collection is an expanded edition of the original 2016, The End of UMNO? It includes the original five essays (including the foreword by current Foreign Minister in the Pakatan Harapan government and former UMNO Supreme Council member Saifuddin Abdullah), as well as new post-GE14 epilogue essays by each of the contributors - John Funston, Clive Kessler, James Chin and Bridget Welsh, all prominent and established scholars studying Malaysian politics. It also includes a new foreword by veteran UMNO leader, Tengku Razaleigh Hamzah, who contested for the party presidency in the June 2018 party elections. The contributors in this collection study developments in Malaysia's dominant party, the United Malays National Organisation (UMNO) and discuss the question of whether UMNO is in fact at an end. The answers to its future lie in part with a better understanding of its past and present. The authors draw attention to issues of party identity, leadership, membership, governance, institutional change, party financing, internal divisions and its relations with different communities and the public at large. The new and expanded edition draws attention to the factors that contributed to UMNO's loss of government in GE14 and potential steps ahead. Not only does this book fill an important gap in the scholarly research on UMNO, this book offers different perspectives on the party's contemporary challenges. This book aims to contribute to understanding, broaden public debate and stimulate further research on arguably one of Malaysia's most important political institutions.